The fourth rule : [large type] a novel - Lindsay, Jeffry P. (Lindsay, Jeffry P. Riley Wolfe series ;, 2023)
"Impossible doesn't belong in Riley Wolfe's vocabulary. He's a master of heists and disguises, whose life's work is swindling the rich out of their undeserved treasures. Now rumors surrounding a dangerous new figure of international crime are spreading through the underworld. And this ruthless collector, the Cobra, has a personal vendetta against Riley ... No matter--with the aid of his new partner, Caitlin, Riley prepares to take on the most powerful cultural institution in the world and bring home the supposedly unstealable Rosetta Stone. With the Cobra waiting for the right moment to strike, Riley is put to the ultimate test as he faces this most venomous villain--and tries to make it out alive"--